The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.09.05.21263141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic and immune markers for precise monitoring of COVID-19 severity and treatment

Abstract: Deep understanding of the SARS-CoV-2 effects on host molecular pathways is paramount for the discovery of early biomarkers of outcome of coronavirus disease 2019 (COVID-19) and the identification of novel therapeutic targets. In that light, we generated metabolomic data from COVID-19 patient blood using high-throughput targeted nuclear magnetic resonance (NMR) spectroscopy and high-dimensional flow cytometry. We find considerable changes in serum metabolome composition of COVID-19 patients associated wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…We and others have reported that COVID-19 patients have altered metabolic pathways and dysregulation of energy production [15][16][17][18][19] . Since plasma metabolites substantially influence the immune cells in shaping protective immune responses, we tested whether levels of specific metabolites or metabolic pathways correlate with the antiviral immune responses.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We and others have reported that COVID-19 patients have altered metabolic pathways and dysregulation of energy production [15][16][17][18][19] . Since plasma metabolites substantially influence the immune cells in shaping protective immune responses, we tested whether levels of specific metabolites or metabolic pathways correlate with the antiviral immune responses.…”
Section: Introductionmentioning
confidence: 86%
“…Since an extensive interplay is reported between plasma metabolites and immune cell activation in COVID-19 patients (15)(16)(17)(18)(19), metabolic analysis in the plasma samples of longitudinal active COVID-19 patients pointed out a set of metabolites significantly correlate with the innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…As such, above all, increased ketone bodies (16), phenylalanine (16,17) and pronounced dyslipidemia with increased ABA1 ratio, decreased HDL cholesterol (16) and decreased apolipoprotein A1 (18) had been mentioned. These markers could help to predict response to therapy (16,19). This was investigated in these two studies with the IL-6 inhibitor tocilizumab, where under and after therapy, respectively, an approximation of the metabolic/lipoproteomic parameters of severe COVID-19 cases to the levels of milder cases was observed.…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, in hospitalized patients with positive outcome, i.e., in Baranovicova et al survivors without respiratory deterioration or mechanical ventilation, normalization of energy metabolism occurred more rapidly, as well as an increase in glutamine, than in patients with negative outcome (deterioration of respiratory situation with need for respiratory support or death). Furthermore, NMR technology has identified markers that may be indicative of a severe COVID-19 progression (10,(16)(17)(18). As such, above all, increased ketone bodies (16), phenylalanine (16,17) and pronounced dyslipidemia with increased ABA1 ratio, decreased HDL cholesterol (16) and decreased apolipoprotein A1 (18) had been mentioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation